NEED-BASED LEARNING MANAGEMENT AT STATE EXCEPTIONAL SCHOOL IN GORONTALO CITY - Lamatenggo, Nina; Haris, Ikhfan; Hadija, Rosita; Razak, Intan Abdul (International Research-Based Education Journal, 2022)
This Study aims to describe: (1) needs-based learning preparation, (2) needs-based learning implementation, and (3) needs-based learning evaluation in State Extraordinary School in Gorontalo City. The study uses qualitative descriptive approach with case study analysis. The study involves 7 respondents including principal, blind teacher, deaf, speech-impaired, mental retardation, Quadri and tetraplegia, autist, and students’ parents. Besides, this study applies in-depth interviews, observation, and documentation. This study consists of data reduction, data display, conclusion, and verification. The study’s findings show that (a) identification / assessment are the efforts done by teachers and the stakeholders to obtain factors that hinder and the competencies that need to be developed in students, (b) Individualized Educational Program (IEP) is an effort to enhance the students’ competencies, (c) learning intervention is one of the efforts done by the school develop the curriculum based on the found obstacles, (d) material modification learning model is the method to adjust the learning subject. In learning implementation, the result shows that (a) teachers’ skill in delivering fun, amusing, and exciting material become an effort to motivate students, (b) the implementation of strategy and method becomes the effort to manage the class based on the obstacles faced by students, (c) source and learning media are supporting a spects in a learning session. Meanwhile, needs-based learning evaluation shows (1) evaluation plan becomes the effort to prepare the predicted questions, the number of question, and the instrument. (2) evaluation implementation is the effort to evaluate the daily task, examination, mid-semester examination, final examination, school’s examination